Wood density and cleaved amplified polymorphic sequence (CAPs) of Acacia SPP - Hafizah, Abdul Razak (Universiti Malaysia Sarawak (UNIMAS), 2012)
(Developing genetically improved plant material of the best adapted plantation species will improve yield and wood quality from the plantations. To assess the quality of Acacia spp. wood available, an understanding of wood properties and genetic analysis of wood quality traits should be done by combining morphological and molecular techniques. Fifty six samples of Acacia hybrid, Acacia mangium Superbulk and Acacia auriculiformis were analyzed with cleaved amplified polymorphic sequence (CAPs) markers and the specific gravity of all samples were. The main objectives of this study were to determine and compare specific gravity of the selected Acacia species from different populations and between the species and to analyze polymorphism of gene (CesAl) using cleaved amplified polymorphic sequence (CAPs)) Determination of specific gravity was carried out in accordance to the American Society for Testing and Material (ASTM) Standard D2395 method B. Two specific primer pairs namely CSI and CS2 were designed based on the full length cDNA of CesAl from A. mangium. Five restriction enzymes, i. e. Alul, Ddel, Dpnl, NIaIV and Bsll which demonstrated the presence of restriction sites and scorable bands were selected for CAPs analysis. The results showed that specific gravity varies with populations and species. A. auriculifomis recorded the highest specific gravity value with 0.55, followed by Acacia hybrid and A. mangium Superbulk with 0.50 and 0.44, respectively. Variation of CAPs profile could be observed from the digestion of CesAl gene region of A. mangium Superbulk from BTSSSB by using Ddel restriction enzymes. Sample SB5 produced a unique banding profile in which an extra fragment (or InDeL polymorphism) of approximately 200 bp was detected. Though InDel polymorphism was detected in this sample, specific gravity data did not correlate with the molecular variation of CesAI gene in A. mangium Superbulk in this study. Further research should be done using more restriction enzymes and more samples of the Acacia spp. should be used.